From New Order to Reformasi: Indonesian Subnational Politics in the Post-New Order Era1 - Leo Agustino; Mohammad Agus Yusoff (Jurnal Hubungan Internasional, 2014)
Direct local election in Indonesia has been run since the middle of 2005. It is bringing some changes, especially in political reformation. Changed election mechanism to direct election done by the society in the region. This article seen that the changes has brought some positive impacts to the society as growing increasingly broad political participation, the legitimacy of local heads becomes higher and political party roles also become important. This changed which the author said as a form of deeper democratic process to “new democracy” in Indonesia. In addition, some weaknesses also appeared, such as the booming of money politic, weaken of regional institution and the emergence of new local elites. It leads to government as a minority in the scope of the power legislative institution which act as majority.